When ‘the Use of Force’ is Prohibited? – Article 2 (4) and the ‘Threshold’ of the Use of Force - Agata (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
This article advances the thesis that there is no threshold of the use of force. i.e. no level of the use of force which decides whether and which forcible actions undertaken by States are prohibited. The examples of actions discussed in the doctrine of law which supposedly would be ‘below’ such a threshold in fact either are regulated by other prin-ciples of international law, are not considered as regulated by ius ad bellum, or States deliberately resign from calling them a use of force for both legal and extra-legal reasons. Thus, the existence of such a threshold is not confirmed by States’ practice. This thesis will be explored using three examples: the cases of the evacuation of nationals, the extra-territorial and the Falklands/Malvinas Islands invasion of 2 April 1982. The article starts with a brief discussion of the opinions expressed in the doctrine of international law on the threshold, as well as the applicable case law.